The third-generation EGFR inhibitor AZD9291 overcomes primary resistance by continuously blocking ERK signaling in glioblastoma - Liu, Xuejiao (J Exp Clin Cancer Res, 2019)
BACKGROUND: Glioblastoma (GBM) is a fatal brain tumor, lacking effective treatment. Epidermal growth factor receptor (EGFR) is recognized as an attractive target for GBM treatment. However, GBMs have very poor responses to the first- and second-generation EGFR inhibitors. The third-generation EGFR-targeted drug, AZD9291, is a novel and irreversible inhibitor. It is noteworthy that AZD9291 shows excellent blood–brain barrier penetration and has potential for the treatment of brain tumors. METHODS: In this study, we evaluated the anti-tumor activity and effectiveness of AZD9291 in a preclinical GBM model. RESULTS: AZD9291 showed dose-responsive growth inhibitory activity against six GBM cell lines. Importantly, AZD9291 inhibited GBM cell proliferation > 10 times more efficiently than the first-generation EGFR inhibitors. AZD9291 induced GBM cell cycle arrest and significantly inhibited colony formation, migration, and invasion of GBM cells. In an orthotopic GBM model, AZD9291 treatment significantly inhibited tumor survival and prolonged animal survival. The underlying anti-GBM mechanism of AZD9291 was shown to be different from that of the first-generation EGFR inhibitors. In contrast to erlotinib, AZD9291 continuously and efficiently inhibited the EGFR/ERK signaling in GBM cells. CONCLUSION: AZD9291 demonstrated an efficient preclinical activity in GBM in vitro and in vivo models. AZD9291 has been approved for the treatment of lung cancer with good safety and tolerability. Our results support the possibility of conducting clinical trials of anti-GBM therapy using AZD9291. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13046-019-1235-7) contains supplementary material, which is available to authorized users.